Catalytic cycle of cytochrome P450s - Roberts, Gordon (Henry Stewart Talks, 2007)
Catalytic cycle of cytochrome P450s, Substrate and oxygen binding, Key electron and proton transfers, Dioxygen cleavage, Formation of the 'activated oxygen' hydroxylating species, Structure and electron transfer properties of NADPH-cytochrome P450 reductase, Possible roles of cytochrome b5 in the p450 monooxygenase system
Archived at 2015/08/14